Data-Driven Market Segmentation: K-means Clustering and STP Analysis in Mainland China’s Sportswear Industry - Mai, Jiajun (International Journal of Global Economics and Management, 2024)
Post-Covid-19, mainland China’s economy is gradually recovering, leading to increased sportswear sales. This study integrates STP theory (segmentation, targeting, positioning) with the K-means clustering algorithm to analyze the sportswear market in mainland China. Consumer data was collected via a questionnaire survey, pre-processed, and cleaned before applying K-means clustering to segment consumers into four distinct groups. The analysis reveals significant differences in purchasing habits across these segments. This data-driven approach offers sportswear companies insights for targeted marketing strategies, enhancing the precision and effectiveness of their marketing efforts in mainland China.